Outcomes Following Transoral Laser Microsurgery With Resection of Cartilage for Laryngeal Cancer. (October 2019) - Chang, Brent A.; Lott, David G.; Nagel, Thomas H.; Howard, Brittany E.; Hayden, Richard E.; Hinni, Michael L.
Introduction: The ability to treat more advanced laryngeal cancers by transoral approaches has expanded significantly in the past several decades. Transoral management of laryngeal cancers that require removal of the laryngeal framework is controversial. Resecting cartilage through endoscopic means carries inherent technical challenges and the question of oncologic safety. Methods: We describe a retrospective review of patients undergoing resection of the thyroid cartilage during transoral laser microsurgery (TLM) for laryngeal cancer over a 10-year period. Only patients with 5-year follow-up were included. Results: Fourteen patients were identified that underwent attempted endoscopic resection of the thyroid cartilage. Preoperative staging ranged from T1 to T4 laryngeal cancers. Most patients underwent resection of the thyroid cartilage either for close proximity of the tumor to cartilage or microscopic involvement of the inner perichondrium, although 6 patients had gross invasion of the cartilage. Twelve patients underwent successful endoscopic clearance. Two patients were converted to total laryngectomy either at the time of surgery or shortly after due to extent of disease that was deemed not amenable to endoscopic resection. Overall 5-year survival was 71%. Disease-free survival was 62% at 5 years. The majority of patients avoided gastrostomy and tracheostomy tube dependence. One patient underwent total laryngectomy following initial TLM for chronic aspiration. Conclusion: We conclude that TLM for laryngeal cancer performed with removal of thyroid cartilage is feasible. Both oncologic and functional outcomes are reasonable in a select group of patients. This paper describes that cartilage can be resected endoscopically in the appropriate setting and not necessarily that cartilage invasion should routinely be treated with TLM.